A parametric study of bubble dynamics and lesion formation in liver tissue phantom during pressure-modulated shockwave histotripsy - Park, Jun Hong; Heo, Jeongmin; Pahk, Kisoo; Pahk, Ki Joo (Nature Publishing Group, 2025)
Pressure-modulated shockwave histotripsy (PSH) is a new type of histotripsy that has recently been proposed for precise mechanical tissue fractionation without inducing the shock scattering effect. Though a previous initial proof-of-concept study clearly demonstrated the feasibility of PSH through introducing the pressure modulation time point (tm) to minimise the shock scattering effect, this study was limited to the examination of the effect of a single PSH pulse at a constant tm on bubble dynamics. Here, we investigated the effects of varying PSH exposure conditions, particularly changes of tm and the number of pulses, on bubble dynamics and lesion formation in liver tissue phantoms. Our experimental results reveal that a gradual increase in tm beyond the time-to-boil can start to initiate shock scattering effect, thereby forming a larger PSH lesion with the transformation of the lesion shape of an ellipsoid to an elongated tadpole. Furthermore, the PSH lesion size gradually increased with PSH pulses. Under the 2 MHz PSH exposure, the smallest oval-shaped lesion area was measured to be 0.18 mm2 with tm of 4 ms and a single PSH pulse, whereas the largest tadpole-shaped lesion area of 5.39 mm2 was produced with tm of 9 ms and 50 PSH pulses. Taken together, these suggest that PSH could be a promising approach for effectively controlling bubble dynamics and lesion formation.